DIFFERENT SHADING ENVIRONMENTS IMPACT GROWTH AND YIELD OF THREE MINI - TOMATO CULTIVARS - DIEGO RANGEL DA SILVA GAMA (Revista Caatinga, 2017)
Our study was conducted in the experimental field of the Department of Technology and Social Sciences (DTCS) of the State University of Bahia - UNEB, Juazeiro - BA. The experimental design was comprised of randomized blocks, sub - subdivided in plots, with four replicates comprising the plots of three different shading methods, gray shading screen (GS), red shading screen (RS), and blue shading screen (BS), and the control treatment with no shading. The subplots comprised three mini - tomato cultivars (“Sweet Million”, “Red Sugar”, and “Shani”), and sub - subplots consisted of seven sampling times. The traits evaluated were: dry matter accumulation in leaves, stems, roots, and fruits, total dry matter, shoot length, root length, total number of fruits, and overall yield. The results of the growth analysis showed that dry matter accumulation in organs of mini tomatoes was similar in all treatments and that the highest total dry matter accumulation occurred under RS. In all treatments, fruit was the preferential drainage; however, the cultivar “Red Sugar” showed higher dry matter accumulation in other plant organs. “Red Sugar” also showed the highest number of fruits per plant; however, when we evaluated total productivity, “Sweet Million” and “Shani” showed similar, higher values than “Red Sugar”.